A9.1 αvβ3 Integrin Inhibition with Cilengitide Both Prevents and Treats Collagen Induced Arthritis. (25th February 2013) - Sykoutri, Despoina; Geetha, Nisha; Hayer, Silvia; Mandl, Peter; S Smolen, Josef; Prager, Gerald; Redlich, Kurt
Abstract : Background: Rheumatoid arthritis (RA) is characterised by synovial inflammation and osteoclast (OC) mediated bone erosions. AlphaVbeta3 (αvβ3) integrin is highly expressed in OCs. Avβ3 blocking antibodies reduce bone resorption and mice lacking β3 are osteopetrotic. Objectives: Efficacy testing of the αvβ3 inhibitor cilengitide, a synthetic Arginine-Glycine-Asparagine amino acid peptide (RGD peptide), on osteoclastogenesis and the collagen induced arthritis (CIA) model for human RA. Materials and Methods: In vitro mouse bone marrow-derived cells (BMCs) were differentiated into tartrate resistant acid phosphatase positive (TRAP+) mononuclear OC precursor cells (pre-OCs) and TRAP+ multinucleated mature OCs with macrophage-colony stimulating factor (M-CSF) and receptor activator of nuclear factor kappaB ligand (RANKL). Cilengitide, was added in increasing concentrations (2 nM to 20 µM) to the culture. These osteoclastogenesis assays were performed on plates coated with RGD containing matrixes osteopontin, fibronectin and fibrinogen but also on Poly-D-lysine to assess αvβ3 independent adhesion. In vivo CIA was induced in 6–8 week old male DBA/1 mice by immunisation with bovine type II collagen at day 1, followed by boosting at day 21. For CIA prevention mice received subcutaneously (s.c.) 1.5 mg/kg cilengitide (n = 15) or placebo (n = 15), 5 days per week, 1 day prior to CIA induction until day 53. For CIA treatment, mice with arthritis were randomised and received 1.5 mg/kg (low dose, n = 19) or 75 mg/kg (high dose, n = 7) cilengitide or placebo (n = 21), until day 59. Preventive and treatment effects were evaluated by assessing paw thickness and grip strength. Results: In vitro increasing concentrations of cilengitide (IC50: 250 nM) dose-dependently reduced pre-OCs on all coatings, indicating early inhibition at the pre-OC proliferation stage. OCs were reduced above 200 nM, followed by complete disappearance above 2 µM. At 200 nM an intriguing morphological difference with reduction in OC size suggested that cilengitide may disrupt spreading and fusion capacity at the early pre-OC stage. In vivo CIA prevention with cilengitide effectively reduced incidence (92.8% versus 40%) and severity of arthritis as evidenced by reduction of clinical disease activity scores. Low and high dose cilengitide effectively inhibited progression of established arthritis. Conclusions: Osteoclastogenesis requires intact αvβ3 integrin function. Systemic αvβ3 integrin inhibition with cilengitide potently prevents and treats experimental CIA. Cilengitide may be a novel therapeutic target in RA.